A randomized phase II trial of personalized peptide vaccine with low dose cyclophosphamide in biliary tract cancer. Issue 5 (5th May 2017) - Shirahama, Takahisa; Muroya, Daisuke; Matsueda, Satoko; Yamada, Akira; Shichijo, Shigeki; Naito, Masayasu; Yamashita, Takuto; Sakamoto, Shinjiro; Okuda, Koji; Itoh, Kyogo; Sasada, Tetsuro; Yutani, Shigeru
Abstract : Since the prognosis of advanced biliary tract cancer (aBTC) still remains very poor, new therapeutic approaches, including immunotherapies, need to be developed. In the current study, we conducted an open‐label randomized phase II study to test whether low dose cyclophosphamide (CPA) could improve antigen‐specific immune responses and clinical efficacy of personalized peptide vaccination (PPV) in 49 previously treated aBTC patients. Patients with aBTC refractory to at least one regimen of chemotherapies were randomly assigned to receive PPV with low dose CPA (100 mg/day for 7 days before vaccination) (PPV/CPA, n = 24) or PPV alone ( n = 25). A maximum of four HLA‐matched peptides were selected based on the pre‐existing peptide‐specific IgG responses, followed by subcutaneous administration. T cell responses to the vaccinated peptides in the PPV/CPA arm tended to be greater than those in the PPV alone arm. The PPV/CPA arm showed significantly better progression‐free survival (median time: 6.1 vs 2.9 months; hazard ratio (HR): 0.427; P = 0.008) and overall survival (median time: 12.1 vs 5.9 months; HR: 0.376; P = 0.004), compared to the PPV alone arm. The PPV alone arm, but not the PPV/CPA arm, showed significant increase in plasma IL‐6 after vaccinations, which might be associated with inhibition of antigen‐specific T cell responses. These results suggested that combined treatment with low dose CPA could provide clinical benefits in aBTC patients under PPV, possibly through prevention of IL‐6‐mediated immune suppression. Further clinical studies would be recommended to clarify the clinical efficacy of PPV/CPA in aBTC patients. Abstract : An open‐label randomized phase II study demonstrated a potential clinical benefit of low dose cyclophosphamide in advanced biliary tract cancer patients treated with personalized peptide vaccination, possibly through inhibition of IL‐6 elevation.